On Generalized p, q-Euler Matrix and Associated Sequence Spaces. (21st June 2021) - Yaying, Taja; Hazarika, Bipan; Mursaleen, Mohammad
Abstract : In this study, we introduce new BK -spaces b s r, t p, q and b ∞ r, t p, q derived by the domain of p, q -analogue B r, t p, q of the binomial matrix in the spaces ℓ s and ℓ ∞, respectively. We study certain topological properties and inclusion relations of these spaces. We obtain a basis for the space b s r, t p, q and obtain Köthe-Toeplitz duals of the spaces b s r, t p, q and b ∞ r, t p, q . We characterize certain classes of matrix mappings from the spaces b s r, t p, q and b ∞ r, t p, q to space μ ∈ ℓ ∞, c, c 0, ℓ 1, b s, c s, c s 0 . Finally, we investigate certain geometric properties of the space b s r, t p, q .